Editorial - Karen Anderson; Martin Baethge; Dieter Sadowski (Journal for Labour Market Research, 2015)
– The current debate about 'Modell Deutschland' has been prompted by the global financial crisis that emerged in 2008 and the Hartz labour market reforms in Germany. Six contributions concerning labour market reform, production systems, vocational education and training, industrial relations, employment patterns, and social policy examine the pillars of the German Model. A central argument in all of the contributions is that the German Model is undergoing a process of recalibration accompanied by increased uncertainty, rather than institutional breakdown. The Model's institutional preconditions and sources of legitimacy are becoming weaker and more questioned than in the past. These processes unfold less via major crises and political interventions than through 'creeping' economic and social changes.
Keywords: 330